Study of Gender Injustice Based on Women's Role as Mother, Wife and Household in The District of Amabi Oefeto, Kupang District - Mariana Ngundju Awang (Humanistic Network for Science and Technology (HNST), 2019)
Background: The reality shows that women experience more disadvantages or disadvantages compared to men in the fields of education, health, employment, mastery and use of science and technology. According to the National Commission on Violence Against Women, the number of cases of violence against women tends to increase from year to year, and reaches more than 348,446 cases of violence against women reported and dealt with during 2017 and perpetrators in the Personal / Private Domain. Method: The type of research used in this study was qualitative research with phenomenological studies of gender injustice variables based on the role of women as mothers, wives and housewives. The information were married women, religious leaders. A number of 20 community and traditional figure with the FGD method and interviews used structured questions compiled by the researchers. Results: Gender inequality is related to the reproductive role of women as mothers, naturally it is true that they carry out this role but there have been changes or shifts where women also carry out gender roles instead men as husbands still assume that women primarily do natural roles but there are also husbands who say women can do other work to support domestic life. The productive role of women as wives has played a role in the public sector but is generally limited to consumption privately and family. The social role of housewives is always involved in community social affairs in the village, only now there are almost no mutual cooperation activities carried out such as In the past, now everyone did work in private in the household. There were and often happened because men felt power and control over women, consider women as helpers who have to do all the work because they have been bought at an expensive price. Men and women alike work both in homes, gardens, fields or fields that the results are enjoyed with the family or can even be sold to buy other necessities in the household such as coffee, sugar, soap and others that are not at home Keywords: gender injustice; reproductive; social roles of women